HUBUNGAN KOMPRES BAWANG MERAH (ALLIN ESENSIAL OIL) DENGAN PENURUNAN DEMAM PADA BALITA DI KAMPUNG HASIK JAYA SORONG SELATAN - Putri, Fatmawati; Wulan, Retno (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022DO - 10.24843/coping.2022.v10.i03.p09, 2022)
Shallots can be used to compress, this is because onions contain organic sulfur compounds, namely allycysteine ??sulfoxide (aliin) which functions to destroy blood clots. Other ingredients of shallots that can lower body temperature are phlorogusin, cycloaliin, methylaliin, and kaemferol. The purpose of this study was the effect of compressing shallots (allin essential oil) on reducing fever in children under five in Hasik Jaya Village, Moswaren District, South Sorong Regency. This type of research is a quasi-experimental research with pre-test and post-test with control group design. The number of samples is 31 respondents. The results showed most of the age of toddlers with fever in Hasik Jaya Village, Moswaren District, South Sorong Regency were 13-24 months as many as 20 toddlers (64,5%), female as many as 18 toddlers (58,1%). Some of the toddlers' temperature before being given red onion compresses (allin essential oil) was 37,8 0 C for 10 toddlers (32,3%). Some of the toddlers' temperature after being given an onion compress (allin essential oil) was 37,5 0 C for 12 toddlers (38,7%). There is a relationship between shallot compresses (allin essential oil) and fever reduction in children under five in Hasik Jaya Village, Moswaren District, South Sorong Regency with p value of 0,000.